Association Between Heart Rate and Major Adverse Cardiovascular Events Among 9,991 Hypertentive Patients: A Multicenter Retrospective Follow-Up Study - Sun, Ningling; Chen, Yuanyuan; Xi, Yang; Wang, Hongyi; Wang, Luyan (Frontiers in Cardiovascular Medicine, 2021)
Objective: To assess the effect of heart rate at baseline on major adverse cardiovascular events (MACEs) among hypertensive patients in China. Methods: A multicenter retrospective study was conducted with a 24-month follow-up period. A total of 10,031 hypertensive patients treated with standard antihypertensive drugs were grouped according to their heart rate before treatment: <65 beats per minute (bpm), 65-69 bpm, 70-74 bpm, 75-79 bpm, and ≥80 bpm. The occurrence of any of MACEs was as the endpoint event during the 24-month follow-up period. The effect of heart rate at baseline on MACEs was analyzed using univate and multivariable Cox proportional regression analyses, with hazard ratios (HRs) and 95% confidence intervals (CIs). The restricted cubic spline (RCS) model was used to fit the Cox proportional harzard model with 5 knots at the 5th, 25th, 50th, 75th, and 95th percentiles of heart rate. Results: Totally 9,991 patients were finally enrolled with the mean systolic pressure (SBP)/diastolic pressure (DBP) of 130.59±7.13/77.66±5.99 mmHg at 24-month follow-up. The incidence of MACEs was 4.80% (n=480). After adjustment for age, gender, baseline blood pressure, alcohol drinking, smoking, hyperlipidemia, diabetes, coronary heart disease, cerebrovascular disease and antihypertensive drug use, patients with heart rate <65 bpm (HR = 1.450, 95% CI: 1.098-1.915) and ≥80 bpm (HR = 1.391, 95% CI: 1.056-11.832) showed 0.45-fold and 0.391-fold increases of MACE risks, compared with patients with heart rate of 70-74 bpm. Furthermore, MACE risks were increased by 86.0% and 65.4% in men, and 59.3% and 69.0% in elderly patients aged ≥65 years at heart rate <65 bpm or ≥80 bpm, respectively. We also found a non-liner U-shaped correlation between heart rate and the occurrence of MACEs. Conclusions: Heart rate might be an independent risk factor for MACEs in hypertensive patients. An appropriate range of heart rate control may offer guidance to hypertension treatment.